RELASI KUASA DALAM PUISI “ENGKAU YANG MENULIS PUISI, AKU YANG MENANDATANGANI” KARYA NIZAR QABBANI DALAM PERSPEKTIF PIERRE BOURDIEU (PENELITIAN KRITIK SASTRA POST-STRUKTULARISME) - Maolidan, Iqbal; Romadhoni, Moh. Syahrul Zaky; Nugraha, Rahmat Mulya (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2022)
One of the famous poets (poetry creators) of his time was Nizar Tawfiq Qabbani (1923-1998) from Damascus. Most of his poetry deals with the themes of romance, politics, and feminism. Unfortunately, literary works are often